Buffalo umbilical cord blood collection and hematological comparison with peripheral blood of new born calf and its dam - Singh, Jarnail; Singh, Vijay; Mann, Anita; Singh, J K; A, Jerome; Sarkar, S K; Dhuan, J S; Yadav, P S (The Indian Journal of Animal Sciences, 2012)
The present study was carried out to explore the feasibility of umbilical cord blood collection and to compare its hematology with peripheral blood of new born calf and the adult buffalo. Jugular blood samples (7) were collected from new born calf and its dam and umbilical cord blood from passed placenta immediately after placental expulsion. These blood samples were analyzed for 22 hematological parameters. Statistical analysis of 22 hematological parameters from all the 3 sources indicated that 7 parameters, viz. WBC, LYM, MON, NEU, HGB, PLT, PCT % of calf and 12 parameters, viz. WBC, LYM, MON, NEU, EOS, BAS, LY %, NE %, HCT %, MCV, MCH, PCT % of adult blood, respectively, were significantly higher than the cord blood, and 3 parameters, viz. RBC, RDWc %, and MO % of adult blood were significantly lower than that of cord blood. A significant difference between cord blood and calf blood with respect to 7 parameters, viz. WBC, LYM, MON, NEU, HGB, PLT, PCT % proves that cord blood and calf blood are not exactly same regarding their cellular content. This difference in hematological parameters of cord blood may be helpful in immunomodulation so that it can be used in transplantation and represent the neonatal defense system against the earliest encountered pathogens.